An identity related to Jordan's inequality - Jian-Lin Li (International Journal of Mathematics and Mathematical Sciences, 2006)
The main purpose of this note is to establish an identity which states that the function sinx/x is a power series of (π2−4x2) with positive coefficients for all x≠0. This enable us to obtain a much stronger Jordan's inequality than that obtained before.